Progresso de phakopsora pachyrhizi em função do estádio fenológico e da idade de trifólios em soja - Augusti, Guilherme Rossato (2012)
Fungicide use with different mechanisms of action as well the pulverization moment are the factors to be considered on the asian soybean rust control. Since many products have shown lost of efficiency, emerges the need of new alternatives to the control of soybean rust. The study aimed to quantify the effect of the systemic resistance inducer Acibenzolar-S-Methyl and the combination of fungicides molecules of the triazole + strobilurin + carboxamide applied in different stages in relation to the soybean rust control and yield. Two field experiments were conducted in greenhouse on the harvest year of 2010/2011. The experiment 1, with the pathogen inoculation at the phenological stage R5.1, was performed on factorial scheme (2x5x6), and the factors consisted of: Factor A: two soybeans cultivars (BMX Potência RR and Coodetec 219 RR); Factor D: treatments with Acibenzolar-S-Methyl (12,5 g a.i.ha-1), Azoxystrobin + Cyproconazole (60 + 24 g a.i.ha-1), Acibenzolar-SMethyl + Azoxystrobin + Cyproconazole (12,5 + 60 + 24 g a.i.ha-1), Pyraclostrobin + Epoxiconazole + Fluxapyroxad (64,8 + 40 + 40 g a.i.ha-1) and a testimony trait in each cultivar; factor E: Application of the treatments at the stages V6, R1, R5.1, 10, 17 and 24 days after the artificial inoculation (DAI) of Phakopsora pachyrhizi. The experiment 2, with the pathogen inoculation at the stage R1 was performed in factorial scheme (2x5x5) differing from the experiment 1 only on the factor E: application of the treatments in R1, 5, 10, 17 and 24 days after the inoculation. Was evaluated the area under the disease progress curve and the number of days to the appearance of the first pustule in leaflets of three distinct ages, also the average weight of seeds per experimental unit. The treatments presented differentiated behavior when exposed to different combinations between the cultivars, application period and leaflets age. Generally the combinations of Acibenzolar-S-Methyl + Azoxystrobin + Cyproconazole and Pyraclostrobin + Epoxiconazole + Fluxapyroxad resulted in better disease control and higher soybeans yield at the earlier and late applications in relation to the pathogen inoculation moment, without differing of Azoxystrobin + Cyproconazole in the others application moments.